Digital assistant for workspace apps - See, Ling Xuan (2022)

(untitled)
Workspace app, or a digital workspace is a technology framework used to deliver, manage, and centrally controls the components of the IT assets of an organization including apps, data, and endpoints. Microsoft Teams, act as an instance of digital workspace is a platform for business collaboration developed by Microsoft to offer functions of workspace chat and videoconferencing, file storage, and application integration to increase an organization’s work efficiency. The problem is that way too many functions to be configured or used in the Microsoft Teams consider time waste to achieve a task with many steps. Besides, the problems include unfamiliar users may apply unsuitable functions in Teams to complete their task and the tedious process to complete a similar task which require repetitive steps. This project proposes a digital assistant to be used in Microsoft Teams for improving efficiency to complete an organization’s task using Teams workspace, by simplifying and giving advisory on steps required to complete a task and automating repetitive tasks. AI and algorithms will be implemented in this project for the digital assistant can have features of understanding towards human’s commands and give suitable output for those commands, to further predict and suggest the future command or possible step may need to be done by the users. Moreover, the digital assistant should allow users to automate tasks by creating and running workflows and using templates. The proposed system will be achieved by applying machine learning to train the digital assistant model for it can study and execute every Teams’ function or the function combinations and allow user customization on its steps to complete certain task. The output of this project will be an AI-based digital assistant designed for simplifying and automating tasks in Microsoft Teams.